Survival of medial versus lateral unicompartmental knee arthroplasty: A meta-analysis. - Seung-Beom Han; Sang-Soo Lee; Kyoung-Ho Kim; Jung-Taek Im; Phil-Sun Park; Young-Soo Shin (PLoS ONE)
Many studies have found associations between unicompartmental knee arthroplasty (UKA) and implant survival, but controversy still exists regarding the relative survival of medial versus lateral UKA over mid-to long-term follow-up. The purpose of this study was to compare survival and clinical outcomes of medial and lateral UKAs. In this meta-analysis, we reviewed studies that assessed implant survival in patients who underwent medial or lateral UKA with short- to mid-term (<10years) or long-term (>10years) follow-up, and that used assessments, such as pain and function scores, to compare postoperative scores on knee outcome scales. A total of eight studies (33,999 knees with medial UKA and 2,853 with lateral UKA) met the inclusion criteria and was analyzed in detail. There were no significant differences between medial and lateral UKA in pain score (95% CI: -0.37 to 0.88; P = 0.42), function score (95% CI: -0.19 to 0.60; P = 0.31), short- to mid-term survival (medial, 32,083/33,483; lateral, 2,636/2,726; OR 0.98, 95% CI: 0.64 to 1.48;P = 0.91), or long-term survival (medial, 479/516; lateral, 110/127; OR 2.51, 95% CI:0.67 to 9.43; P = 0.17). In addition, both groups had substantial proportions of knees with short- to mid-term survival (95.6% by medial UKA and 94.6% by lateral UKA) and long-term survival (92.8% by medial UKA and 86.6% by lateral UKA). This meta-analysis found no significant differences in short- to mid-term and long-term survival of medial and lateral UKAs. Similarly, patients treated with medial UKA showed no difference in pain relief or functional improvement compared to patients treated with lateral UKA. These results suggest that both UKA techniques are viable treatment options for patients with unicompartmental knee osteoarthritis over long-term follow-up, although further high-quality studies are needed to address some remaining uncertainties regarding the clinical benefits of these procedures.